A Comparison of Text, Voice, and Screencasting Feedback to Online Students. Issue 3 (2nd July 2016) - Orlando, John
ABSTRACT: The emergence of simple video and voice recording software has allowed faculty to deliver online course content in a variety of rich formats. But most faculty are still using traditional text comments for feedback to students. The author launched a study comparing student and faculty perceptions of text, voice, and screencasting feedback. The results provide some interesting insights into the advantages and disadvantages of different forms of feedback. The author finishes with best practices for providing screencasting feedback to students.